Signatures of Adaptation and Acclimatization to Reef Flat and Slope Habitats in the Coral Pocillopora damicornis - Marhoefer, Shelby R.; Zenger, Kyall R.; Strugnell, Jan M.; Logan, Murray; van Oppen, Madeleine J. H.; Kenkel, Carly D.; Bay, Line K. (Frontiers in Marine Science, 2021)
Strong population-by-habitat interactions across environmental gradients arise from genetic adaptation or acclimatization and represents phenotypic variation required for populations to respond to changing environmental conditions. As such, patterns of adaptation and acclimatization of reef-building corals are integral to predictions of the future of coral reefs under climate warming. The common brooding coral, Pocillopora damicornis, exhibits extensive differences in host genetic and microbial symbiont community composition between depth habitats at Heron Island in the southern Great Barrier Reef, Australia. An 18-month reciprocal field transplant experiment was undertaken to examine the environmental and genetic drivers behind variation in survival, weight gain, heat tolerance and algal symbiont community between the reef flat and slope habitats. We observed population-by-habitat interactions for in situ partial mortality and weight gain, where trait-related fitness of natives was greater than transplants in most cases, consistent with local adaptation. On average, flat colonies transplanted to the slope had a relatively low partial mortality but minimal weight gain, whereas slope colonies transplanted to the flat had relatively high partial mortality and average weight gain. Experimental heat tolerance was always higher in colonies sourced from the flat, but increased when slope colonies were transplanted to the flat, providing evidence of acclimatization in these colonies. The performance of certain slope to flat transplants may have been driven by each colony’s algal symbiont (Symbiodiniaceae) community, and flat variants were observed in a small number of slope colonies that either had a fixed flat composition before transplantation or shuffled after transplantation. Host genotypes of previously identified genetic outlier loci could not predict survival following transplantation, possibly because of low sample size and/or polygenic basis to the traits examined. Local environmental conditions and Symbiodiniaceae composition may provide insight into the adaptive potential to changing environmental conditions.